Horizontal Transmission of the Symbiont Microsporidia MB in Anopheles arabiensis - Nattoh, Godfrey; Maina, Tracy; Makhulu, Edward E.; Mbaisi, Lilian; Mararo, Enock; Otieno, Fidel G.; Bukhari, Tullu; Onchuru, Thomas O.; Teal, Evan; Paredes, Juan; Bargul, Joel L.; Mburu, David M.; et al. (Frontiers in Microbiology, 2021)
The recently discovered Anopheles symbiont, Microsporidia MB, has a strong malaria transmis-sion-blocking phenotype in Anopheles arabiensis, the predominant Anopheles gambiae species complex member in many active transmission areas in eastern Africa. The ability of Microsporidia MB to block Plasmodium transmission together with vertical transmission and avirulence makes it a candidate for the development of a symbiont-based malaria transmission blocking strategy. We investigate the characteristics and efficiencies of Microsporidia MB transmission between An. ara-biensis mosquitoes. We show that Microsporidia MB is not transmitted between larvae but is ef-fectively transmitted horizontally between adult mosquitoes. Notably, Microsporidia MB was only found to be transmitted between male and female An. arabiensis, suggesting sexual horizontal transmission. In addition, Microsporidia MB cells were observed infecting the An. arabiensis ejac-ulatory duct. Female An. arabiensis that acquire Microsporidia MB horizontally are able to transmit the symbiont vertically to their offspring. We also investigate the possibility that Microsporidia MB can infect alternate hosts that live in the same habitats as their An. arabiensis hosts, but find no oth-er non-anopheline hosts. Notably, Microsporidia MB infections were found in another primary malaria African vector, Anopheles funestus s.s. The finding that Microsporidia MB can be trans-mitted horizontally is relevant for the development of dissemination strategies to control malaria that are based on the targeted release of Microsporidia MB infected Anopheles mosquitoes.